Surgical Site Infection Following Single-Port Appendectomy: A Systematic Review of the Literature and Meta-Analysis - Köhler, Franziska; Reese, Lena; Kastner, Carolin; Hendricks, Anne; Müller, Sophie; Lock, Johan F.; Germer, Christoph-Thomas; Wiegering, Armin (Frontiers in Surgery, 2022)
Introduction: Surgical site infections (SSI) are one of the most common postoperative complications after appendectomy leading to recurrent surgery, prolonged hospital stay and the use of antibiotics. Numerous studies and meta-analysis have been published on the effect of open versus conventional laparoscopic appendectomy (CLA) reporting faster postoperative recovery and less postoperative pain for CLA. A development from conventional laparoscopic appendectomy has been the single port appendectomy, associated with a better cosmesis but seemingly having a higher risk of wound infections. Aim of this systematic literature review and meta-analysis is to investigate whether reduced port or single port appendectomy (SPA) alters the ratio of surgical site infections. Methods: Pubmed, Embase and Cochrane databases were screened for suitable articles. All articles published between January 1th 2002 and March 23rd 2022 were included. Articles regarding children below the age of 18 were excluded as well as manuscripts that investigated solemnly open appendectomies. Articles were screened for inclusion criteria by two independent authors. Incidence of SSI was primary outcome. Duration of operation and length of hospital stay were defined as secondary outcomes. Results: 25 studies were found through database search describing 5484 patients. 2749 patients received SPA and 2735 CLA. There was no statistical difference in the rate of SSI (P = 0.98). 22 studies including 4699 patients reported the duration of operation (2223 SPA and 2476 CLA). There was a significant shorter operation time seen in CLA. Length of hospital stay was reported in 23 studies (4735 patients, 2235 SPA and 2500 CLA). Shorter hospital stay was seen in the SPA group (P < 0.00001). Separately performed analysis of randomized controlled trials could not confirm this effect (P = 0.29). Discussion: SPA is an equally safe procedure considering SSI compared to CLA and does not lead to increased risk of SSI. Longer operation time for SPA and minor difference in the length of stay does lead to the use of SPA in selected patients only.